IN TURKISH DIDACTIC LITERATURE: TRADITION AND INNOVATION - Amira Shukurova (Journals Park Publishing, 2022)
In Turkish literature, which has a long and rich history, didactic or instructive works have a special position. The literary and educational heritage of Yusuf Khos Hajib, Ahmad Yugnaki, Ahmad Yassavi, Alisher Navoi, who are major representatives of Turkish didactic literature, are considered the most important monuments of literature in the spirit of pandnoma. In this article, Adib Ahmad Yugnaki's work "Hibat ul-haqayq" in the later period of pandnoma literature, the works created by Alisher Navoi, the issue of the influence of wisdom in the formation of ideas such as the perfect person, the just king, and the just society described in them, is highlighted.
Keywords: epic, research, impact, didactics, analysis, source, interpretation, tradition, literature.